2005
DOI: 10.1128/aem.71.12.8165-8173.2005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fermentation Medium Composition on Physicochemical Surface Properties of Lactobacillus acidophilus

Abstract: The effect of the simple and complex basic components of a fermentation medium on the surface properties of Lactobacillus acidophilus NCC2628 is studied by physicochemical methods, such as electrophoresis, interfacial adhesion, and X-ray photonelectron spectroscopy, and by transmission electron microscopy. Starting from an optimized complete medium, the effect of carbohydrates, peptones, and yeast extracts on the physicochemical properties of the cell wall is systematically investigated by consecutively omitti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
54
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 43 publications
5
54
0
Order By: Relevance
“…Schar-Zammaretti (2005) suggested that S-layer protein is preferentially expressed under different fermentation media. Furthermore, it has been shown that the S-layer production is changed with the change in medium (such as bile salt, penicillin G) (Khaleghi et al, 2010(Khaleghi et al, , 2011.…”
Section: Probiotics and Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…Schar-Zammaretti (2005) suggested that S-layer protein is preferentially expressed under different fermentation media. Furthermore, it has been shown that the S-layer production is changed with the change in medium (such as bile salt, penicillin G) (Khaleghi et al, 2010(Khaleghi et al, , 2011.…”
Section: Probiotics and Stressmentioning
confidence: 99%
“…There is some evidence that the surface properties of microorganisms are dependent on the growth conditions and the composition of the fermentation medium (Schar-Zammaretti et al, 2005;Waar et al, 2002;Dufrene & Rouxhet, 1996;Millsap et al, 1997). Schar-Zammaretti (2005) suggested that S-layer protein is preferentially expressed under different fermentation media.…”
Section: Probiotics and Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, detailed analyses of the relationship between LAB cell wall constituents and physicochemical properties are slowly emerging. It has been demonstrated that components of growth medium (such as yeast extract and peptones) present an important factor in determining the surface properties of lactobacilli, including structure and physicochemical characteristics of bacterial cell wall [10]. A better knowledge of these aspects could help us understand the roles that different cell surface constituents have in bacterial behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The surface properties of bacteria are vital for their survival and interactions with the environment, including that with other microorganisms and host organisms [10]. Frequently, the behavior of LAB is dependent on the cell surface physicochemical properties and their chemical composition [11].…”
Section: Introductionmentioning
confidence: 99%